Association between gut microbiota and ultra-processed foods consumption among the patients with type 2 diabetes: a cross-sectional study - Takahiro Ichikawa; Yoshitaka Hashimoto; Yusuke Igarashi; Sayaka Kawai; Ayumi Kaji; Ryosuke Sakai; Takafumi Osaka; Ryo Inoue; Saori Kashiwagi; Katsura Mizushima; Kazuhiko Uchiyama; Tomohisa Takagi; et al. (Nutrition & Metabolism)
Abstract Background This study aimed to explore the relationship between ultra-processed foods (UPFs) consumption and gut microbiota in patients with type 2 diabetes (T2D). Methods This cross-sectional study included 362 participants with T2D. UPFs consumption was assessed using a brief-type self-administered diet history questionnaire, quantified as the density of UPFs intake (g/1000 kcal). Gut microbial composition was evaluated via 16S rRNA gene sequencing. We investigated the association between gut microbiota, previously identified as relevant to T2D, and the density of UPFs intake using Spearman rank correlation coefficients. Multiple regression analysis, adjusting for age, sex, BMI, smoking status, exercise, and medication use, was conducted to further investigate these associations. Results The mean age of participants was 68 (63–74) years. The density of UPFs intake showed significant associations with Bifidobacterium (r = 0.11, p = 0.031), Lactobacillus (r = 0.11, p = 0.046), Ruminococcus (r = −0.12, p = 0.019), Roseburia (r = 0.11, p = 0.045). After adjusting for covariates in multiple regression analysis, Ruminococcus and Roseburia showed modest negative (β = −0.11, p = 0.038) and positive (β = 0.12, p = 0.033) correlations, with the density of UPFs intake among participants with T2D, respectively. Conclusions The density of UPFs intake was modestly inversely associated with Ruminococcus among patients with T2D and modestly positively associated with Roseburia.